Teacher and Student Opinions on Online Mathematics Education - SONMEZKALE, Ipek; OZRECBEROGLU, Nurdan; GEZERCAN, Yelda SERIN; GUNES, Gunsel CAKIR (Asian Journal of Contemporary Education, 2022)
As a result of the Covid-19 virus becoming a pandemic in the world, all countries affected by the epidemic, as well as the Turkish Republic of Northern Cyprus (TRNC), have been affected by education, leading to the use of distance education over face-to-face education in order to slow down the spread of the virus in educational structures. According to the opinion of mathematics teachers and students, this study was conducted to identify both positive and negative aspects of the online mathematics lesson in light of these developments. In the research, descriptive survey design, one of the qualitative research methods, was used. Semi-structured interview forms were used to collect data from sixty-five students and eleven mathematics teachers. The data of the research were analyzed by content analysis. According to the results it can be said that, it has been stated that online education of the students creates an important advantage.